Challenges in Cervical Cancer Prevention: Real-World Scenario in India - Kaur, Satinder; Sharma, Lalit Mohan; Mishra, Vinita; Goyal, Maj Gen Bhupesh; Swasti, Swasti; Talele, Avinash; Parikh, Purvish M. (South Asian Journal of Cancer, 2023)
In spite of global falling trends, cervical cancer remains a major healthcare challenge for India, South Asia Association for Regional Cooperation region, and other low- and middle-income countries. Our survey was to document the real-world challenges that still exist in India. A total of 316 eligible and complete responses to the 21 questions were analyzed. Screening of mothers and vaccinating their daughters was considered as the most important strategy to prevent cervical cancer by 65.8% (208/316). Screening was offered to all asymptomatic eligible females by 79% (250/316). Improvement in screening rates requires promoting the national program (67.7%; 214/316), strengthening existing infrastructure (62%; 196/316), regular training of primary healthcare workers (57.6%; 182/316), and increasing awareness among schools and colleges (57.9%; 183/316). Almost all responders (93%; 294/316) wanted to have human papillomavirus (HPV) vaccination included in the national immunization schedule. Cost of vaccine was considered a major roadblock. If it became available at INR 250 per dose, 96.8% (306/316) respondents would recommend it for all eligible patients. With the impending availability of this indigenous tetravalent HPV vaccine jointly produced by Department of Biotechnology, Govt of India and Serum Institute of India, the war against cervical cancer just got easier.
Keywords: HPV; vaccination; public health; VILI; VIA